Avances en el conocimiento de la sarcocistiosis de camélidos sudamericanos y desarrollo de herramientas para su control - Decker Franco, Cecilia (2019)
South American camelids (SAC) are an attractive livestock that provides benefits to the\nAndean communities. Meat is the main source of protein for these communities. Unfortunately, SAC\nare infected by Sarcocystis aucheniae that produces rice grain like macrocysts that give an unpleasant\nappearance causing economic losses.\nA PCR was developed capable of detecting DNA of S. aucheniae with high specificity and\nsensitivity in blood of llamas, but in turn this method was applied to detect DNA of the parasite in\nother SAC as well as in fecal matter of dogs. Although this method resulted unuseful as a diagnosis\ntool pre-slaughter, it can be useful in epidemiological studies, to evaluate the effectiveness of the\ntreatments with parasiticides, and for the surveillance and localization of the definitive hosts.\nOn the other hand, the transcriptome of S. aucheniae was sequenced and several bioinformatic\nanalyzes were carried out to search for candidate proteins to be used as antigens for diagnosis, creation\nof drugs and immunotherapy approaches.\nThis thesis provides original and relevant information on S. aucheniae, a parasite practically\nforgotten by the scientific community, as well as innovative diagnostic tools, which may have\nimportant implications for the strengthening of the Andean economies.